2019
DOI: 10.1016/j.jwpe.2019.100787
|View full text |Cite
|
Sign up to set email alerts
|

Water recovery from inorganic solutions via natural freezing and melting

Abstract: MMXVII AbstractA combined natural freezing and melting water recovery process was evaluated for a 0.5 molal magnesium sulphate solution. 500 mL of solution was placed in a container open to the air, and the temperature was lowered to between -2 and -26 °C. At equilibrium the solid produced, consisting of ice and entrapped solution or solute crystals, was removed and thawed at either 3 °C or 25 °C. The resulting liquid was analysed for magnesium. Microscopy of the solid was also performed. Although the purity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…At the same time, the presence of the ice cover makes the water less disturbed and more stationary. The migration of malathion from the ice to the under-ice water causes a concentration gradient between the ice growth front and the under-ice water, resulting in a "constitutional undercooling" [ 47 ]. Constitutional undercooling creates suitable conditions for dendritic ice growth ( Figure 6 ) [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the presence of the ice cover makes the water less disturbed and more stationary. The migration of malathion from the ice to the under-ice water causes a concentration gradient between the ice growth front and the under-ice water, resulting in a "constitutional undercooling" [ 47 ]. Constitutional undercooling creates suitable conditions for dendritic ice growth ( Figure 6 ) [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, ice melting was performed at room temperature and therefore melted faster compared to the actual lake ice melting. At lower ambient temperatures, the initial melting out of solutes would be more pronounced [ 54 ]. Atrazine is relatively concentrated in ice encapsulated in salt cells or channels, rather than uniformly distributed within the ice body.…”
Section: Discussionmentioning
confidence: 99%
“…Sci. 2024, 14,36 After polynomial fitting of the centrifugal time and centrifugal speed, it can be seen that the two factors have a good correlation with the salt rejection, with correlation coefficients (R 2 ) of 0.95541 and 0.98476, respectively (Figure 8). At the same time, using analysis of variance (ANOVA), it can be concluded that the correlation between salt rejection and centrifugal time (p = 0.007, F = 45.292) and centrifugal speed (p = 0.026, F = 16.747) is high, and the p-values are all less than 0.05 (Table 2), indicating a significant correlation.…”
Section: Research On the Desalination Effect Of The Fcm On Waste Leac...mentioning
confidence: 98%
“…During the freezing process, the water in the solution freezes in solid form, while the solutes are more inclined to be retained in the non-ice phase of the concentrate, and with the prolongation of the freezing time, the ice crystal structure grows and gradually excludes the solutes, thus improving the salt rejection [14]. Figure 1 shows the variation in the water quality parameters at different freezing times.…”
Section: Freezing Parameter Settingsmentioning
confidence: 99%